TYPOLOGICAL CHARACTERISTICS OF ENGLISH, UZBEK AND KARAKALPAK FOLK RIDDLES - Khojanova Nargul Jenisbayevna; Kerwenov T. (Journals Park Publishing, 2023)
This article provides information about riddles that are examples of folklore, their place in the Uzbek, English and Karakalpak languages, and their typological features.
Keywords: riddles, tipological, Uzbek, folklore, English, Karakalpak.